Microbes Associated to Dyer’s woad (Isatis tinctoria L.): Pigment Extraction, Dyeing and Cultivation with Non-toxic Inputs. A Review - Yli-Hemminki, Pirjo; Pihlava, Juha-Matti; Leppälä, Johanna; Keskitalo, Marjo (Springer Nature, 2025)
Dyer’s woad (Isatis tinctoria L.) is a biannual plant cultivated mainly for its leaves, which are source of precursors of natural blue pigment known as indigo. Pigment extraction and dyeing with indigo have traditionally been mediated by bacteria. Specifically, indigo-reducing bacteria convert the pigment to its soluble form, which then drifts to the water-immersed textile material in a vat dyeing process. Upscaling these microbial processes to an industrial scale, requires an understanding of how the appropriate bacterial community is applied and maintained in an anoxic, alkaline and hot vat system. Bacteria enter the system with leaf material and may originate from the soil. Therefore, bacterial communities, which have been extensively studied in Japanese indigo dyeing baths usually differ from those derived from European woad. Currently, characterised indigo-reducing bacterial isolates are available and recombinant microbes for indigo biosynthesis have been developed to replace synthetic and often toxic chemicals in the blue dye industry. Woad is defending its place in crop rotation, breaking monoculture as a functional allelopathic plant or as a nutrient scavenging catch crop, even in northern latitudes. High-yielding cultivars can be introduced into crop sequences, and indigo can be extracted on the farm to generate additional income for farmers’ cooperatives.
Keywords: allelopathy; Brassicaceae; indigo-producing bacteria; indigo-reducing bacteria; vat dyeing